Eventos de seca na região Sudeste do Brasil: ocorrências temporais e comportamento futuro - Silva, Vinicius Oliveira (2018)
Droughts are climatic phenomena that may strongly affect a given region. Its effects may be observed in different areas such as agriculture, livestock, water supply, and tourism. This study aimed to analyze, based on the Standard Precipitation Index (SPI) and the Standard Precipitation Evapotranspiration Index (SPEI), the drought events that had affected three of the greatest Metropolitan Brazilian regions (São Paulo, Campinas, and Belo Horizonte), south of Minas Gerais State region (Lavras) and the central-east region of São Paulo State (Piracicaba) in the past. In addition, the study aimed to analyze the future occurrence of drought events based in two different Global Climate Models, Eta-MIROC5 and Eta-HadGEM2-ES, and two different scenarios (RCP 4.5 and RCP 8.5) until 2099. The results have shown that the most severe drought episodes in the studied region occurred throughout the hydrological years of 2013-2014 and 2014-2015. The comparison of the two studied indexes have shown that the SPEI is more sensitive to drought events, since it takes into account the temperature for its calculation. It is recommended to use the SPEI index for the city of São Paulo, since the region is more sensitive to the effects of temperature than the other cities studied. For the cities of Lavras, Nova Lima, Campinas and Piracicaba, it was observed that the results of SPI and SPEI are similar and both indices may be used to identify drought episodes. The drought episodes simulated by the Eta-HadGEM2-ES model are concentrated in blocks, with several events occurring consecutively, while the Eta-MIROC5 has shown a intercalation between positive and negative SPI. The SPEI index simulations were similar to the SPI for the Eta-MIROC5, however this behavior was not noticed for the Eta-HadGEM2-ES, wherein the temperature is a important factor. The Eta-HadGEM2-ES RCP 8.5 simulated the worst drought scenario, where the temperature climbs until the end of the 21st century. Thus, it was evidenced that the southeastern Brazil presents a highlighted climate vulnerability to severe drought episodes and the understanding of the nature of these phenomena through climate models can be significant to subsidize the public and private companies to implement actions aiming to reduce the harm effects of extreme/severe droughts in the future.